Abdominal Vagal Afferents Modulate the Brain Transcriptome and Behaviors Relevant to Schizophrenia - Klarer, Melanie (J Neurosci, 2018)
Reduced activity of vagal efferents has long been implicated in schizophrenia and appears to be responsible for diminished parasympathetic activity and associated peripheral symptoms such as low heart rate variability and cardiovascular complications in affected individuals. In contrast, only little attention has been paid to the possibility that impaired afferent vagal signaling may be relevant for the disorder's pathophysiology as well. The present study explored this hypothesis using a model of subdiaphragmatic vagal deafferentation (SDA) in male rats. SDA represents the most complete and selective vagal deafferentation method existing to date as it leads to complete disconnection of all abdominal vagal afferents while sparing half of the abdominal vagal efferents. Using next-generation mRNA sequencing, we show that SDA leads to brain transcriptional changes in functional networks annotating with schizophrenia. We further demonstrate that SDA induces a hyperdopaminergic state, which manifests itself as increased sensitivity to acute amphetamine treatment and elevated accumbal levels of dopamine and its major metabolite, 3,4-dihydroxyphenylacetic acid. Our study also shows that SDA impairs sensorimotor gating and the attentional control of associative learning, which were assessed using the paradigms of prepulse inhibition and latent inhibition, respectively. These data provide converging evidence suggesting that the brain transcriptome, dopamine neurochemistry, and behavioral functions implicated in schizophrenia are subject to visceral modulation through abdominal vagal afferents. Our findings may encourage the further establishment and use of therapies for schizophrenia that are based on vagal interventions. SIGNIFICANCE STATEMENT The present work provides a better understanding of how disrupted vagal afferent signaling can contribute to schizophrenia-related brain and behavioral abnormalities. More specifically, it shows that subdiaphragmatic vagal deafferentation (SDA) in rats leads to (1) brain transcriptional changes in functional networks related to schizophrenia, (2) increased sensitivity to dopamine-stimulating drugs and elevated dopamine levels in the nucleus accumbens, and (3) impairments in sensorimotor gating and the attentional control of associative learning. These findings may encourage the further establishment of novel therapies for schizophrenia that are based on vagal interventions.